I imagine I been science fiction always - Kearney, Douglas (Wave books (Seattle, Wash.), 2025)
"On the heels of Sho (winner, Griffin Poetry Prize) and Optic Subwoof (Pegasus Award in Poetry Criticism), Douglas Kearney's visual poetry masterpiece, I Imagine I Been Science Fiction Always, pushes further into Kearney's long-time practices of performance typography, collaging pre-existing media sources to create singular, multiplicitous texts that defy neat categorization. Through AfroFuturistic exploration of these techniques, Kearney presents a sustained consideration of precarious Black subjectivity, cultural production as self-defense, the transhistoric emancipatory logics of the preposition over, Anarcho-Black temporal disruption, and seriocomic meditations on the material and metaphysical nature of shadow. Engaging a rich history of visual poetics, I Imagine I Been Science Fiction Always almost predicts its endurance as a visionary work of genius"--